2019
DOI: 10.1001/jamasurg.2018.3865
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Role of Lymph Node Positivity and Number of Lymph Nodes Needed for Accurately Staging Small-Bowel Neuroendocrine Tumors

Abstract: IMPORTANCE Little information is available regarding the minimum number of lymph nodes needed to accurately stage patients when performing a mesenteric lymphadenectomy for small-bowel neuroendocrine tumors. OBJECTIVES To determine the prognostic role of lymph node positivity and the ideal number of lymph nodes for accurately staging patients with small-bowel neuroendocrine tumors. DESIGN, SETTING, AND PARTICIPANTS This case series from the US Neuroendocrine Tumor Study Group, a collaboration among 8 US-based, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
63
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 29 publications
6
63
1
1
Order By: Relevance
“…In fact, TNLE among patients with pancreatic and small bowel NETs relative to recurrence-free survival and overall survival has been examined by our group and others. 15,24 Using a large multi-institutional database with external validation based on the surveillance, epidemiology, and end results (SEER) registry, we demonstrated that TNLE ≥ 8 had the highest discriminatory power relative to recurrence-free and overall survival among patients with pNET who hadone to three LNM, and patients who had ≥4 LNM in both a multi-institutional data set and the SEER database. 15 In the current study, we similarly noted that TNLE ≥ 8 had the strongest discriminatory power to ensure identification of possible LNM and optimally stage the nodal basin for patients with dNETs.…”
Section: Tumor Size and Nodal Metastasismentioning
confidence: 98%
“…In fact, TNLE among patients with pancreatic and small bowel NETs relative to recurrence-free survival and overall survival has been examined by our group and others. 15,24 Using a large multi-institutional database with external validation based on the surveillance, epidemiology, and end results (SEER) registry, we demonstrated that TNLE ≥ 8 had the highest discriminatory power relative to recurrence-free and overall survival among patients with pNET who hadone to three LNM, and patients who had ≥4 LNM in both a multi-institutional data set and the SEER database. 15 In the current study, we similarly noted that TNLE ≥ 8 had the strongest discriminatory power to ensure identification of possible LNM and optimally stage the nodal basin for patients with dNETs.…”
Section: Tumor Size and Nodal Metastasismentioning
confidence: 98%
“…The impact of lymph node positivity in neuroendocrine tumors also may not be uniform across all disease sites. Our group recently reported that there is limited prognostic significance of lymph node positivity in small bowel neuroendocrine tumors if fewer than 4 lymph nodes are positive . It is important to note that the average number of positive lymph nodes in this study was 3.4 and 3.8 in small bowel neuroendocrine tumors for Black and White race patients, respectively.…”
Section: Discussionmentioning
confidence: 50%
“…In the literature, there are many studies aiming to define prognostic or predictive markers in this heterogeneous group of tumor (4-7). Primary tumor site, stage, grade, age, primary tumor size and lymph node involvement have been shown to predict disease outcome in previous studies (8,9). Of these factors, grade and are the most reliable prognostic parameters and stage strongly correlate with survival (10,11).…”
Section: Introductionmentioning
confidence: 95%